Perbaikan Prestasi Menghafal Melalui Pendampingan Keluarga Dan Penguatan Motivasi Santri - jazilah, khoirul; Bashiroh, Ainul (Amaliyatu Tadris, 2025)
This classroom action research aims to improve students’ Qur’anic memorization performance through two main strategies: family involvement and motivation enhancement. The study was initiated in response to the low level of memorization achievement among students, which was influenced by the lack of parental support in supervising daily muraja’ah as well as weak intrinsic motivation. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were students of the Tahfiz Program at Darun Najah Sarionggo Islamic Boarding School. Data were collected through observations, memorization tests, motivation questionnaires, interviews, and family monitoring journals The results demonstrate a significant improvement in memorization achievement. In the pre-cycle stage, only 50% of students reached the expected level of memorization. After the implementation of Cycle I, which included structured muraja’ah routines and family monitoring journals, the achievement increased to 70%. In Cycle II, further enhancement of intrinsic motivation through personal guidance, motivational stories, and strengthened communication with parents resulted in a 90% achievement rate. These findings indicate that the integration of parental involvement and motivational strategies is highly effective in improving both the quality and consistency of Qur’anic memorization. This study affirms that collaborative support and well-directed motivation are essential components for successful tahfiz learning.